The Structure of Tolerance Education in the Process of Multicultural Education (Journal of Pedagogical Inventions and Practices, 2023)
In this article discusses about socio-cultural identification of an individual, the study of historical stories, local traditions, ethical standards will be effective bdies; dialogue and so on will be particularly important in mastering the concepts of multiculturalism - lectures, Christian conversations, working with sources; developing intercultural communication abilities.